Retelling time: alternative temporalities from premodern South Asia - Kaul, Shonaleeka (Routledge, Taylor & Francis Group, 2022)
1. Temporality and Its Discontents Or Why Time Needs to be Retold / Shonaleeka Kaul -- 2. The Moment in Which the River Rests: Time in Early Buddhism / Gergana Rumenova Ruseva -- 3. Proleptic Pasts and Involuted Causalities in Kūṭiyāṭṭam / David Dean Shulman -- 4. Taking, Making, and Leaving: The Many Times of the Āyāraṃga / Christoph Emmrich -- . 5 The Guru and the Mantra: Transcending Time in the Philosophy and Practice of Yoga / Tarinee Awasthi -- 6. Time is Born of his Eyelashes: Purāṇic Measurement and Conceptions of Time / McComas Taylor -- 7. On Rasa and Recursivity: Ethics and Aesthetics of Time in Sanskrit Poetics (alaṃkāraśāstra) / Shonaleeka Kaul -- 8. Sun, Consciousness and Time: The Way of Time and the Timeless in Kashmir Śaivism / Bettina Sharada Baümer -- 9. Time is in the Moment (waqt) and also in Eternity (dahr): Reflections from Sufi Islam / Kashshaf Ghani -- 10. Concentric Worlds: Space and Time in the Pratyabhijñā school and the Abhinavabhāratī / Radhika Koul -- 11. Corporal Time to Cognitive Time: Kannada Wordscape in Transition 10th to 13th centuries / Manu V. Devadevan -- 12. (Un)doing Space and Time: 'Doing' the Rāmcaritmānas / Aditya Chaturvedi -- 13. The Ontology of Now: Reading Time through 16th and 17th century Nyāya philosophy / Samuel Wright -- 14. 'A Farrago of Legendary Nonsense': Myth, Time and History in the Keralolpatti / Dilip M. Menon -- 15. The Knots of Time: Reading Nostalgia in Bengali Literature from 13th to the 19th century / Anuparna Mukherjee.
Keywords: South Asia -- Civilization; Aufsatzsammlung; Zeit; Chronologie; Literatur; Indische Sprachen; Südasien; Indische Philosophie